Parental stature as a risk factor for stunting in Indonesia: A systematic review and meta-analysis - Amriviana, Mazaya P.; Khairunnisa, Cut; Sasongko, Teguh H. (Narra J, 2023)
Stunting is defined by height of more than two standard deviations below the WorldHealth Organization's (WHO) child growth standard median. It is a significant nutritionalproblem in developing countries, where in 2021, Indonesia recorded a stunting prevalenceat 24.4%, slightly higher than the global prevalence (22%). Reducing the prevalence ofstunting has been the focus of the current administration in the Indonesian government,as delineated in the 2020–2024 National Medium-Term Development Plan. Globally,many studies have addressed parental stature as a risk factor of stunting. However,systematic reviews that summarized and critically appraised the relationship betweenparental stature and the incidence of stunting in Indonesia was scarce. This systematicreview aimed to assess parental stature as a risk factor for stunting among Indonesiantoddlers. Studies were searched through PubMed (MEDLINE), Google Scholar andMendeley. Studies on Indonesian toddlers under five years old living in Indonesia wereincluded. The quality of the included studies was assessed using Joanna Briggs Institute(JBI) critical appraisal tool. Data were extracted using a standardized data extraction formand were analyzed using Cochrane’s RevMan 5.3. Twenty-seven prospective andretrospective cohort, case-control and cross-sectional studies were included with a total4041 children. Out of 27 included studies, eight were found to be of low, seven of moderateand twelve of high quality. The result showed that parental stature was associated with theincidence of stunting among toddlers in Indonesia, either the mother only (odds ratio(OR) 1.92; 95% confidence interval (95%CI: 1.71–2.15), the father only (OR 5.21; 95%CI:1.71–15.86) or both parents (OR 3.01; 95%CI: 2.41–3.75). However, studies on father andboth parental statures suffered from substantial heterogeneity, imprecision and mixedqualities, therefore, they should be cautiously interpreted.